"We keep quiet": exploring the context of pregnancy intention in a low-resource community in Ecuador. Issue 1 (1st January 2019) - Feld, Hartley; Rojas, Verónica; Linares, Ana Maria
Abstract: Unintended pregnancies are both a consequence and a cause of socioeconomic inequality. Family planning prevents unintended pregnancy and reduces health disparities. The purpose of this study is to describe the structural, social, economic context of pregnancy intention in a peri-urban, diverse, low-resource community in Ecuador. A qualitative descriptive methodology was used. Semi-structured individual interviews were performed with 19 female participants of reproductive age. Interviews were professionally transcribed in Spanish, translated into English, and analysed in MAXQDA using content analysis. The majority of pregnancies were reported as unintended and four themes emerged to describe the context. (1) Women's autonomy is limited by men, (2) Women keep quiet, (3) Systems failed women, and (4) Building resilience. Health systems, gender-based violence, limited education and financial means, and policies yet to be enforced served as barriers to both empowerment and family planning. In spite of this, many women were able to transition into safety, and prevent or delay pregnancy with new partners. Ecuador has made significant economic gains in the past two decades, but these findings suggest that inequality persists in some regions of Ecuador. The women in this study report needing to feel safe, productive and valued to plan their families. Public health professionals need to involve multi-sectors in solutions to reduce health disparities and address determinants of maternal/child health including gender-based violence, economic and systemic limitations. DOI:10.1080/26410397.2019.1686198